Pengaruh Implementasi Kebijakan Pemerintah Finlandia Terkait Oxford Coronavirus Government Response Tracker (OxCGRT) Terhadap Penanganan COVID-19 - Trinita Estetika Sigalingging; Rozmita Dewi Yuniarti Rozali (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2020)
This study aims to determine the effect of policies issued by the Finnish government to deal with the Covid-19 pandemic. Through analysis, the enforcement of policies related to OxCGRT can have an impact regarding the handling of Covid-19. These impacts include the suppression of the growth rate of Covid-19 cases, an increase in the recovery of Covid-19 cases, as well as other impacts related to Finnish governance. The method used in this study is library research. Based on research that has been done, can be concluded that the Finnish government has implemented good governance in terms of handling this Covid-19 case with the implementation of all existing policies such as the closure of educational facilities and workplaces, cencelation of events and public meetings, closure of all non essential businesses, travel restrictions, policies to conduct testing, and stay at home policies. The implication of this study is as consideration for every element in a country to handle the Covid-19 case. The limitation of this study is the lack of literature on this topic so researchers are quite difficult to obtain data.